Comprehensive transcriptional analysis of ethylene and softening regulation in plums with distinct climacteric ripening behaviors - Huang, Po-Kai; Manganaris, George A.; Gasic, Ksenija; Saski, Christopher A.; Beckles, Diane M; Crisosto, Carlos H. (My University, 2025)
Understanding the molecular mechanisms underlying variations across climacteric categories in tree crops remains challenging, particularly due to the limitations of applying conventional genetic approaches. In this study, we examined genetically related Japanese plum (Prunus salicina Lindl.) cultivars with distinct ethylene production and responses during ripening: 'Santa Rosa' (climacteric fruit), 'Casselman' (suppressed-climacteric fruit), and 'Sweet Miriam' (non-climacteric fruit). Our primary objective was to comprehensively investigate transcriptional differences related to ethylene and fruit softening across three on-tree developmental stages: "Green" (early development), "Mature" (pre-climacteric or early climacteric), and "Ripe" (climacteric). By integrating information from Phytozome and Dicot PLAZA databases, we identified complete gene families for six ethylene-related and seven softening-related genes. Multi-developmental stage RNA-seq clustering revealed that "Late" genes, which increase in expression in ripe fruit, are associated with physiological differences among climacteric categories. We demonstrated that 'Casselman' aligns more closely with 'Sweet Miriam' than 'Santa Rosa' at the transcriptional level for these "Late" genes, consistent with their shared low ethylene production. Gene expression analyses revealed additional factors beyond ethylene, including jasmonate-related genes and NAC transcription factors as influencing climacteric ripening behavior. To extend our findings beyond the three representative cultivars, we performed qPCR on additional cultivars harvested under different field conditions and years, including 'Friar' and 'Fortune' as climacteric plums and 'Late Santa Rosa' and 'Angeleno' as suppressed-climacteric plums. PpACO1, PpPL1, PpBGAL16, PpNAC2, and PpJID1 expression patterns were conserved across cultivars and experimental conditions. Our findings provide novel insights into the transcriptional regulation of climacteric ripening and offer a strategic framework for future genetic studies in plum and other tree crops.
Keywords: Prunus salicina; Climacteric; Ethylene; Fruit softening; Non-climacteric; Suppressed climacteric; Transcriptional regulation